The effects of lubricant eye drops on visual function as measured by the Inter-blink interval Visual Acuity Decay test - Gail Torkildsen (Dove Medical Press, 2009)
Gail TorkildsenAndover Eye Associates, Andover, MA, USAObjective: The purpose of the current study was to evaluate the effects of two marketed ocular lubricants on the visual decay in dry eye patients using the Inter-blink interval Visual Acuity Decay (IVAD) test.Methods: This controlled, randomized, double-masked crossover study compared the effects of a polyethylene glycol/propylene glycol-based (PEG/PG) tear and a carboxymethylcellulose sodium (CMC)/glycerin tear on the visual acuity decay between blinks of dry eye patients. At visit 1 (Day 0), baseline IVAD measurements were recorded prior to instillation of a single drop of randomized study medication. IVAD testing was repeated at 15-, 45-, and 90-minutes post-instillation. Reading rate and functional blink rate were also evaluated. At the second visit (Day 7 ± 3), study procedures were repeated using crossover treatment.Results: Forty-eight (48) subjects with dry eye (61.1 ± 14.8 years old, 79.2% female, 95.8% white) completed the study. Treatment with the PEG/PG-based tear demonstrated statistically significantly longer time to one-line loss of best-corrected visual acuity (BCVA) as determined by the IVAD test at 90 minutes post-instillation compared to the CMC/glycerin tear (P = 0.0365). Measurements of median time at BCVA, reading rate, and functional blink rate were similar for both treatments. Both formulations were well tolerated in the population studied.Conclusions: Treatment with the PEG/PG-based tear demonstrated statistically significant improved maintenance of visual acuity between blinks at 90 minutes post-instillation compared to the CMC/glycerin tear. This is the first study to demonstrate the ability of an artificial tear to extend visual acuity maintenance between blinks, as measured by the IVAD test.Keywords: dry eye, visual function, artificial tears, ocular lubricant